2008
DOI: 10.1158/0008-5472.can-07-1580
|View full text |Cite
|
Sign up to set email alerts
|

t-Darpp Promotes Cancer Cell Survival by Up-regulation of Bcl2 through Akt-Dependent Mechanism

Abstract: t-Darpp is a cancer-related truncated isoform of Darpp-32 (dopamine and cyclic-AMP-regulated phosphoprotein of M r 32,000). We detected overexpression of t-Darpp mRNA in two thirds of gastric cancers compared with normal samples (P = 0.004). Using 20 Mmol/L ceramide treatment as a model for induction of apoptosis in AGS cancer cells, we found that expression of t-Darpp led to an increase in Bcl2 protein levels and blocked the activation of caspase-3 and caspase-9. The MitoCapture mitochondrial apoptosis and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 45 publications
2
78
0
2
Order By: Relevance
“…In addition, knockdown of t-DARPP resulted in a significant decrease of pAKT and BCL2 protein levels that can also explain the role of t-DARPP in cell survival in this particular cell model. We have recently shown that t-DARPP expression up-regulates BCL2 through CREB/ATF-dependent mechanism that requires active AKT in gastric cancer cells (20). BCL2 protein is a pivotal regulator of apoptotic cell death that counteracts drug-induced apoptosis and shifts the balance toward cancer cell survival through stabilization of the mitochondrial transmembrane potential and inhibition of cytochrome c release and activation of caspases (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knockdown of t-DARPP resulted in a significant decrease of pAKT and BCL2 protein levels that can also explain the role of t-DARPP in cell survival in this particular cell model. We have recently shown that t-DARPP expression up-regulates BCL2 through CREB/ATF-dependent mechanism that requires active AKT in gastric cancer cells (20). BCL2 protein is a pivotal regulator of apoptotic cell death that counteracts drug-induced apoptosis and shifts the balance toward cancer cell survival through stabilization of the mitochondrial transmembrane potential and inhibition of cytochrome c release and activation of caspases (21).…”
Section: Discussionmentioning
confidence: 99%
“…28 E2F1 has been suggested to be able to regulate Bcl2 expression through activating Akt. 29,30 To test the molecular linkage of miR-26a-HMGA2-E2F1-Akt-Bcl in the signaling pathway that regulates cell resistance to CDDP, we suppressed the expression of HMGA2 in A549 using a siRNA approach. As shown in Fig.…”
Section: Mir-26a Inhibits E2f1 and Akt Pathwaymentioning
confidence: 99%
“…Hypergeometric test is a type of command statement in the software. For example, we aimed to identify a list of 30 genes from the entire genome of 20000 genes, and 5 genes are related to cycle, while there are totally 200 cell cycle genes in the genome, then the decimal p-value will be: p=exp(log_hypergeometric (5,30,200,20000). A low Pvalue indicates that the observed CR value is unlikely to occur by chance and the pathway exhibits a greater than expected trend toward participating in CDDP resistance.…”
Section: Identification Of Potential Active Tf-mirna Regulatory Pathwmentioning
confidence: 99%
“…91 Bcl-2 expression can be regulated by activated CREB, 92 and the regulation of Bcl-2 by Akt and CREB is implicated in drug resistance. 93 Thus, mutations that eliminate PTEN activity could contribute to therapy resistance by deregulated CREB activity, leading to altered Figure 2 Interactions between PI3K/PTEN/Akt/mTOR pathways that result in the regulation of protein translation. The PI3K/PTEN/Akt/mTOR pathway can affect protein translation by complex interactions regulating the mTORC1 and mTORC2 complexes.…”
Section: Downstream Targets Of Akt Regulating Mtor Activitymentioning
confidence: 99%